The Effect of Public Service on Community Satisfaction at the Department of Agriculture, Food Crops and Horticulture, West Aceh, Indonesia - Yulia, Risma; Ikhsan, Ikhsan; Fadhly, Zuhrizal; Hajad, Vellayati (Utan Kayu Publishing, 2022)
This study aims to determine that public services have an effect on community satisfaction at the Department of Agriculture, Food Crops and Horticulture, West Aceh. This research was conducted using quantitative research methods with data sources from 25 respondents. The data analysis technique used the community satisfaction index (IKM) calculated using the weighted average value of each service and satisfaction indicator. The results of this study indicate that the IKM for services at the Department of Agriculture for food crops and horticulture can be said to be in good condition at 61.78, thus proving that H0 is rejected. So it can be concluded that there is a real influence between the public service variable (x) on the satisfaction variable (y).